PENGARUH WEIGHT TRAINING SISTEM PIRAMID TERHADAP HASIL LOMPAT JAUH PESERTA DIDIK SMA SANTUN UNTAN - Agus Malinda; Ahmad Atiq; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe problem in this research is that students when jumping always drop from one of the back of the body, lack of muscle explosive power when doing jumps and students are still lacking in throwing legs forward so the jumps are less than optimal. The purpose of this study was to determine the effect of the pyramid system weight training on the results of the long jump of students in Sma Santun Untan Pontianak.The method used in this research is an experiment with a one group pretest –posttest design. It designs that is used to determine the effect of a treatmen on reserch subjects. The data analysis use a t-test.The population in this study were students in senior high school of Santun Untan Pontianak class IX with a total of 90 people. Sampling’s method using purposive technique, which amounted to 30 students in the senior high school of Santun Untan Pontianak as an experimental class. Data analysis techniques using t-test. The result of the research obtained an average pretest value of 3,05  meters and average posttest value of 3,22 meters. Analysis of the data in the value of the pretest and posttest is 0,17. Ut means that the second hypothesis is accepted, it means that there is in influence of the weight training system of the pyramid on the long jump results of students is Santun Untan Pontianak High School.      Keywords: Pyramid System Weight Training, Long Jump Results.